Results-Based Monitoring and Evaluation and Knowledge Management Approaches in Government to Government Partnerships: The Case of the Shandong and WCG Partnership - Chen, Xue Qing; Coning, Christo De; Pretorius, Leon (Journal of Reviews on Global Economics, 2019)
Government to Government (G2G) partnerships between countries in the BRICS partnerships have significantly increased and with it, the need for more effective evidence-based decision-making. In this process, improved M&E and KM has become prominent. In this context, the study investigated the need for Monitoring & Evaluation (M&E), as well as knowledge management (KM) systems in partnerships. This study focused on the development management aspects of such partnerships and the article is based on research information obtained through the PhD study by Dr Ivy Chen as well as updated research perspectives. The article concluded that a need existed to establish more advanced M&E and KM systems in G2G partnerships. The Readiness Assessment conducted regarding M&E showed that a need existed for Results-Based M&E that can be used to ensure evidence-based decision-making in the G2G partnerships. The Readiness Assessment showed that a definite need existed for Communities of Practice (COPs) beyond the formal meetings and that professionals and practitioners on both sides needed to exchange explicit and implicit knowledge. A need also existed for improved ICTs based-systems including dedicated portals where policy documentation, programme information and data, as well as M&E results, can be loaded and shared by Governments.